Harvesting of Autogenous Bone Graft from the Ascending Mandibular Ramus Compared with the Chin Region: a Systematic Review and Meta-Analysis Focusing on Complications and Donor Site Morbidity - Thomas Starch-Jensen; Daniel Deluiz; Sagar Deb; Niels Henrik Bruun; Eduardo Muniz Barretto Tinoco (eJournal of Oral Maxillofacial Research)
Objectives: The aim of this systematic review was to test the hypothesis of no difference in complications and donor site morbidity following harvesting of autogenous bone graft from the ascending mandibular ramus compared with the chin region.